Fermentation Characteristics of Rice Crop Residue-Based Silage Treated by Epiphytic and Commercial LAB - B Santoso; B Tj Hariadi; . Alimuddin; D Y Seseray (Media Peternakan, 2012)
Two experiments were conducted to investigate the effects of addition of lactic acid bacteria (LAB) inoculant from king grass and a commercial inoculant of L. plantarum on fermentation characteristics and nutrient digestibility of rice crop residue-based silage. In experiment 1, mixture of rice crop residue (RC), soybean curd residue (SC) and cassava waste (CW) in a 80 : 10 : 10 (on dry matter basis) ratio was used as silage material. Four treatments silage were (A) RC + SC + CW as a control; (B) RC + SC + CW + LAB inoculant from king grass (2%, v/w) ; (C) RC + SC + CW + LAB inoculant from king grass (3%, v/w); (D) RC + SC + CW + L. plantarum inoculant (2%, v/w). In experiment 2, six Kacang goats were used in a 6 × 3 Youden square experiment and fed elephant grass, rice straw, and rice crop residue-based silage. The results showed that crude protein (CP) content in silages B, C, and D was slightly higher than silage A. Lactic acid concentration was significantly higher (PL. plantarum inoculant.